Premixed calcium-phosphate cement pastes - Takagi, Shozo; Chow, Laurence C.; Hirayama, Satoshi; Sugawara, Akiyoshi (Journal of biomedical materials research. Part B, Applied biomaterials, 2003)
A self‐hardening calcium–phosphate cement (CPC) containing Ca4(PO4)2O and CaHPO4 has been shown in clinical studies to be efficacious for repairing bone defects. This and several other similar CPCs harden in 10 min with the use of a phosphate solution as the liquid and form hydroxyapatite (HA) as the product. The present study investigated the properties of water‐free, glycerol‐containing CPC pastes that are stable in the package and would harden only after being delivered to a defect site where glycerol–tissue fluids exchange occurs. Premixed CPC pastes were prepared by combining cement liquids containing glycerol and various amounts of hydroxypropyl methylcellulose/Na2HPO4, with CPC powders that contained (1) Ca4(PO4)2O and CaHPO4, (2) α‐Ca3(PO4)2 and CaCO3, or (3) CaHPO4 and Ca(OH)2. The hardening times and 1‐d and 7‐d diametral tensile strengths were measured on samples that hardened in an in vitro model that allowed exchange of glycerol and physiologic‐like solution (PLS) through fritted glass slides at 37 °C. All pastes had excellent washout resistance; they remained intact and hardened while immersed in PLS and formed HA as products. Newman–Keuls multiple comparison tests indicated that the Na2HPO4 amount, not the hydroxypropyl methylcellulose (HMC) amount, significantly (p < 0.05) affected the strength and hardening time. Although the premixed CPCs generally have longer hardening times and lower strengths, these pastes have excellent washout resistance before hardening and can be prepared in advance under well‐controlled conditions. © 2003 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 67B: 689–696, 2003